Hubungan Burnout terhadap Dampak Produktivitas Kinerja Perawat di RSUD Ir. Soekarno Sukoharjo - Putri, Erni Fatmawati; Astuti, Andriani Mei; Widiastuti, Agung (TRIAGE Jurnal Ilmu Keperawatan, 2025)
Burnout is a state of physical, emotional, and mental exhaustion that arises due to high and prolonged work pressure, especially in professions with high levels of work intensity such as nursing. This condition has a significant impact on reducing the enthusiasm, motivation, and productivity of nurses, which ultimately affects the quality of nursing services in hospitals. This study aims to identify the relationship between burnout and decreased work productivity of nurses in the Inpatient Ward of Ir. Soekarno General Hospital, Sukoharjo Regency. This study applies a quantitative method with a cross-sectional research design. The number of respondents consisted of 69 nurses, selected using a purposive sampling method. The tools used in the study consisted of the Maslach Burnout Inventory (MBI) questionnaire to assess the level of burnout and a work productivity questionnaire that has six indicators: ability, work results, motivation, self-development, quality, and efficiency. The research findings indicate that the majority of respondents experienced burnout in the high category (66.7%) and low work productivity (89.9%). Bivariate analysis using the Spearman Rank test produced a p-value of 0.001 < 0.05. The higher the level of burnout experienced by nurses, the lower their work productivity in completing nursing tasks effectively and sustainably. Workload management, strengthening social support, rewarding performance, improving work-life balance, and regular stress management training can support maximum performance and improve the quality of care services comprehensively and sustainably in addressing burnout